Getting your shot : stunning photos, how-to tips, and endless inspiration from the pros. (Washington, D.C : National Geographic Society, 2015)
Full of tips, ideas, advice, and amazing photographs, this new, inspirational, how-to photography book is the next best thing to having a National Geographic photographer as your personal instructor.
Catch the light -- Self-portrait -- Home -- Spontaneous adventure -- The animals we love -- After midnight -- Foodscapes -- Love snap -- Iheart my city -- Biodiversity -- Family portrait -- The moment -- Embrace the untamed -- Explore our changing world -- Nature in black & white -- How close can you get? -- Imagine if.
Keywords: PHOTOGRAPHY -- MISCELLANNEA